Cost‐Effective Hierarchical Cobalt Nanostructured Laser‐Induced Graphene for Enhanced Uric Acid Detection - Anju Joshi; Gymama Slaughter (Advanced Sensor Research, 2025)
Abstract This study presents an innovative, cost‐effective strategy to develop a flexible, enzyme‐free biosensor for the sensitive detection of uric acid (UA). Utilizing electrochemically modified cobalt nanostructured on laser‐induced graphene electrodes (CoNCs/LIG), this approach surpasses traditional noble metal‐based electrocatalysts in sensitivity and affordability. The one‐step electrochemical modification method is efficient and straightforward, enabling the uniform deposition of hierarchical flower‐like cobalt nanostructures. These structures synergistically enhance the performance of the LIG, resulting in a broad detection range of 5 to 700 µM with a sensitivity of 6.75 µA µM−1 cm−2 and a low detection limit of 3.66 µM for UA. The morphology and elemental composition of the CoNCs/LIG electrodes are characterized using scanning electron microscopy (SEM) and energy‐dispersive X‐ray spectroscopy (EDS). Beyond sensitivity, the sensor exhibited excellent selectivity, reliably resisting interference from competing biologically species such as ascorbic acid, dopamine, glycine, and glucose. Clinical utility is demonstrated in serum and artificial urine samples, achieving recovery rates ranging from (102.47%–104.46%). This work highlights the exceptional electrocatalytic efficiency of CoNCs/LIG‐based flexible biosensors, offering a highly sensitive, selective, and cost‐effective platform for UA detection, with promising applications in clinical diagnostics and health monitoring.